Implications of the Peer Instruction Type Flipped Classroom Learning Model with Traditional Flipped to Improve Learning Outcomes of Science - Aslamiyah; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2025)
The results of observations conducted by researchers at SDN Gisikdrono 02 Semarang show that students are less active in participating in classroom learning, especially in science subjects. This contributes to their low learning outcomes. To overcome this problem, The purpose of this study is to compare the effectiveness of the peer instruction type flipped classroom learning model with the traditional flipped model in improving student learning outcomes on science material in grade V SDN Gisikdrono 02 Semarang. This study employed a quasi-experimental approach with data collection methods utilized in this study included observations, interviews, and documentation. According to the results of the hypothesis testing using the independent sample t-test, the significance value. (2-tailed) which is smaller than α = 0.05 (0.000 < 0.05). This indicates that H0 is rejected in favor of Ha. Based on the calculation of the N-Gain score, the experimental and control classes scored 0.63 and 0.39, which are both included in the medium category. Based on the N-Gain percent criteria, the experimental class with a score of 63% is said to be quite effective, while the control class with a score of 39% is said to be ineffective. This outcome Suggests that the execution of peer instruction type Instructional model in the experimental class is more effective than the traditional flipped model in the control class.